Incorporating mechanical, electrical and plumbing systems into historic preservation projects - three case studies - Terry, Jason (Kansas State University, 2008)
Architectural engineers face many challenges in the design and implementation of mechanical, electrical, lighting, plumbing, and fire protection systems in buildings. Space and aesthetic coordination must be managed between the architects, engineers, contractors, and building owners. Further design issues are involved when renovating or preserving historic properties. Historic buildings often contain additional design limitations and character defining features that must be preserved. A building's character defining features often represent past history, culture, and architecture. To better understand the design coordination and other issues faced in historic renovation, three case studies located in Kansas City, Missouri, are presented to investigate the application of mechanical, electrical, and plumbing (MEP) system design into historic buildings. The three case studies include: the Stowers Institute for Medical Research, as a mechanical design; the Union Station, as an electrical and lighting design; and the Webster House, as a plumbing and fire protection design. The renovation projects' architects, engineers, and contractors were personally interviewed to obtain the most accurate information and account of the design and construction process. Additional information was gathered, and a tour of each building allowed for the pictorial documentation of each site. Preserving the historic character of buildings during renovations has many advantages and disadvantages for both the owners and the designers. The additional design parameters in historic renovation projects foster creative thinking and problem solving during the design and construction process. In order to implement a successful design, the architects, engineers, and contractors must work together and understand the value of a building's historic character during the design stage when adapting to a new usage.
Keywords: Architectural engineering; Preservation; Stowers Institute; Union Station; Webster House; MEP systems; Architecture (0729); Engineering, General (0537)